CVD grown bi-layer MoS2 as SERS substrate: Nanomolar detection of R6G and temperature response - Pada Majee B.; Jangra P.; Kumar Mishra A. (My University, 2025)
The two-dimensional bi-layer MoS2 is less investigated as compared to monolayer and few-layer (4–6 layers) MoS2 for fundamental aspects and applications such as photodetectors, transistors, etc. In the present work, we prepare triangular-shaped bi-layer MoS2 over SiO2/Si substrate via chemical vapour deposition (CVD) technique for surface enhanced Raman scattering (SERS) based detection of Rhodamine 6G (R6G). We perform density functional theory calculations and spectroscopy studies to investigate the semiconducting feature of bi-layer MoS2. We demonstrate the nanomolar concentration (10-9 M) limit for R6G detection at room temperature using pristine bi-layer MoS2 as SERS substrate. Further, we also examine the cryogenic response of the SERS detection of R6G with bi-layer MoS2 for the first time. The high detection limit of CVD-grown bi-layer MoS2 is ascribed to the charge transfer enabled via vibronic coupling between MoS2 and R6G molecules. This study paves the way for cryogenic-based SERS sensing. © 2024 The Authors